Jobs gained and lost through trade: The case of Germany - Maren Lurweg; Andreas Westermeier (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
The nature of international trade has changed significantly. For centuries, trade concentrated on the exchange of finished goods. It now increasingly involves bits of value that are added at different locations to combine into one final product. Therefore, trade in functions or tasks are of growing importance and exports of final goods are no longer an appropriate indicator of the international competitiveness of countries. The process of globalisation has an impact on domestic labour markets. Due to the increasing integration of the world economy, some jobs are gained and others lost in any open economy. Concerns about German workers losing jobs to foreign competition dominate many political debates. Many people fear that being integrated in the world economy is disadvantageous for Germany. In this paper, we use input-output analysis to explore the relationship between trade and both job creation and job destruction in Germany over the period 1995-2006. We present two main findings. First, in an autarkic situation, around 7.0 per cent of total German jobs would not have existed at all in 2006. The job effect of trade was positive in every reporting year. Second, the manufacturing sector contributed most to this positive job effect, but also in the service sector, many jobs were retained through trade.
Keywords: F14; F16; C67; 330; input-output analysis; international trade; employment